Epidemiological and clinical profile of people hospitalized for HIV/AIDS in the department of Meta - Colombia (Boletín Semillero de Investigación en Familia, 2022)
Introduction: since its first diagnoses in the 80s of the 20th century, HIV / AIDS was established as an event of interest in public health and the clinical field, which, due to the technological advance that has been achieved through Of the time, when treated with antiretroviral therapy, it has gone from being a rapidly progressive catastrophic disease to a chronic disease. with incidence figures worldwide that have sustained it as a pandemic. Objective: to describe the epidemiological characteristics and some clinical manifestations of people with a diagnosis of HIV / AIDS; that were treated in the two public hospitals in the department of Meta, Colombia, between 2014 and 2019. Methods: cross-sectional, observational epidemiological study; from secondary sources. Results: the median age was 38 years (IQR 29 - 49), 20.4% of the cases corresponded to women, the residence was mainly in urban areas (85.6%), the subsidized health system insurance regime predominated with the 63.9%. Admissions to hospitalization for infectious signs and symptoms was 82.4%. Anemia (66.3%) and thrombocytopenia (45.5%) presented the highest incidence in the blood line alteration. The median CD4 T lymphocyte count was 61.5 cells / mm3 IQR (22.7 - 186.2). Undetectable viral load was found in 3.7% of reported cases. More than half of the cases studied did not receive ART before their last hospitalization. Conclusions: in the institutions that provide public health services of greater complexity that exist in the department of Meta; Mainly young men were cared for, who presented symptoms of constitutional syndrome at hospital admission; More than half of the cases did not receive ART before the last hospitalization, this being a condition for the decrease in the quality of life of PLWHA.
Keywords: HIV; acquired immunodeficiency síndrome; clinical manifestations; epidemiology.